Optimalisasi Peningkatan Komunikasi Lewat Program Training Untuk Usaha Mikro, Kecil, Dan Menengah (UMKM), Komunitas Kepemudaan Dan Mahasiswa - Nandaryani Damastutik; Siti Aminah (Politeknik Kampar, 2023)
Soft skills training is a program designed to improve and develop soft skills such as interpersonal, leadership, communication, collaboration, adaptability, creativity, and other non-technical skills. This study aims to make a positive contribution in improving communication skills within the scope of SMEs, communities and students. This community service research aims to identify the optimization of one of the BCTI unit programs, namely Raising the Level of Speech which is given to MSMEs, Communities and Students. By using a qualitative descriptive method, because the research focus is to describe and provide an overview of the information on the object being studied. The research that has been done has shown that the Speech Level Raise training program is running effectively. Because participants who took part in the training experienced increased speaking skills and felt helped and useful for their needs. This program is also aligned with Sustainable Development Goal 4, namely Quality Education which ensures inclusive and equitable quality education and promotes lifelong learning opportunities for all.